167k views
18 votes
THanks again everyone ​

THanks again everyone ​-example-1
User Jpyams
by
5.2k points

2 Answers

4 votes

Check option B

  • Passes through (0,-1)

So

  • 3y-4x=-3
  • 3(-1)-4(0)=-3
  • -3=-3

Hence verified

Option B is correct

User Cguenther
by
4.8k points
0 votes

Answer:

option B shows the correct solution.

Find y-intercept:

3y - 4x = -3

3y - 4(0) = -3

3y = -3

y = -1

Find x-intercept:

3y - 4x = -3

3(0) - 4x = -3

-4x = -3

x = 3/4

THanks again everyone ​-example-1
User Studentu
by
4.7k points